INTERNALISASI NILAI NILAI HADITS KEBERSIHAN DALAM PENDIDIKAN ANAK USIA DINI - Jazariyah Jazariyah (MASILE, 2019)
This study aims to discuss the internalization of hadith values in early childhood. Using a qualitative descriptive approach this research was conducted at PAUD IT An Najah Klaten. Data analysis was obtained from the results of interviews, observation and documentation of activities. The data obtained were then analyzed and resulted in the conclusion that PAUD IT An Najah conducted a program of Clean and Healthy Life Behavior (PHBS) as an effort to internalize the value of hygiene hadith values. Some PHBS activities carried out include: Hand Washing with Soap (CTPS) both before and after activities, brushing teeth, consuming healthy snacks by setting the snack time menu, using clean and healthy latrines and disposing of garbage in its place.